Immature/transitional B-cell expansion is associated with bone loss in HIV-infected individuals with severe CD4+ T-cell lymphopenia. (1st August 2020) - Titanji, Kehmia; Ofotokun, Ighovwerha; Weitzmann, M. Neale
Abstract : Background: Antiretroviral therapy (ART) has led to a significant decline in HIV-related morbidity and mortality in people living with HIV (PLWH). PLWH however experience non-AIDS ageing-associated comorbidities, including decreased bone mass and osteoporosis, earlier and more severely, than uninfected people. We previously reported that total B-cell production of the key osteoclastogenic cytokine receptor activator of NF-κB ligand (RANKL) was elevated in PLWH, concurrent with a decrease in total B-cell production of RANKL's physiological moderator Osteoprotegerin (OPG). The resulting increased total B-cell RANKL/OPG ratio was significantly associated with bone loss in the appendicular (long bones), but not axial (spine) skeletons of PLWH. A role for immature/transitional B cells (BImm ) in HIV-induced bone loss has not been reported. Methods: BImm frequency was determined by flow cytometry; plasma IL-7 was quantified by ELISA and bone mineral density (BMD) measured by dual X-ray absorptiometry (DXA) in a cross-sectional study of 62 ART-naive HIV-infected and 58 HIV-negative individuals. Results: BImm expansion correlated with the total B-cell RANKL/OPG ratio in HIV-infected individuals and inversely with BMD at the total hip, femoral neck and the lumbar spine, and with IL-7. Conclusion: These data suggest that BImm contribute to the increased B-cell RANKL/OPG ratio in PLWH, and reveal a previously unrecognized link between BImm expansion and HIV-induced bone loss in the axial and appendicular skeletons of severely immunocompromised HIV-infected individuals. BImm expansion may be a novel biomarker for screening patients at risk of osteoporosis.